(untitled) (Annual of the Faculty of Philosophy in Skopje, 2016)
First discovered in the 18th century, the uranium is a natural element that is found everywhere on Earth, but mainly in trace quantities, although in the Earth’s crust there are regions where there is an increased concentration of uranium ore. The uranium ore may be dug underground or with surface methods, depending on the depth where is located. With ISL method the ore is mixed with an acid to dissolve uranium after which it separated from the solution. The final product ofphase of digging and crushing or ISL, is a concentrate of uranium oxide (U308). Due to the high density the uranium is used in the keel of ships and as a counterweight in aircraft control surfaces, as well as a shield against radiation and production of armored piercing ammunition. Like other elements, the uranium occurs in slightly different forms known as isotopes. These isotopes (16 in the case of uranium) differ from each other in the number of particles (neutrons) in the nuclei. Natural uranium that is found in the Earth’s crust is mainly a m ixture of two isotopes: U-238 represented with 99.284% and U -235 to about 0.711%. The 238 U decays very slowly, its half-life is the same as the age of the earth. This means that it is virtually indestructible. DU which consists of 99.8% of238U is obtained as by-product in the process of enrichment of uranium, and is classified as toxic and radioactive waste. In sufficient quantities, DU could be harmful because of its chemical toxicity. As mercury, cadmium and other heavy metal ions, the excess uranium ions suppress renal function. High concentrations in the kidneys can damage them and in extreme cases can cause their failure. Chemical toxicity of DU prevents studying his internal body radiological effects. Because DU is mild radioactive, once entered the body it radiates the organs. It is known that high doses of radiation cause cancer. It is generally accepted for radiological protection purposes that low doses of radiation cause cancer too, but as the dose is lower so the risk is lower. If the DU lump is being hold in hand, radiation dose to the skin, which comes mainly from beta particles can easily be reduced by wearing gloves, or if DU is enclosed in another material. To cause radiation burns or other promptly effects in this case the DU should act for months. The theoretical maximum for the whole body irradiated with y external dose, which could be achieved in practice, is in vehicles that are DU armored and equipped with DU ammunition. But even then, the crew at about 1000 hours would be dosed similar to the average annual total dose of natural radiation that occurs in some countries.